Structural Determinants of Ubiquitin-CXC Chemokine Receptor 4 Interaction - Saini, Vikas (American Society for Biochemistry and Molecular Biology, 2011)
Ubiquitin, a post-translational protein modifier inside the cell, functions as a CXC chemokine receptor (CXCR) 4 agonist outside the cell. However, the structural determinants of the interaction between extracellular ubiquitin and CXCR4 remain unknown. Utilizing C-terminal truncated ubiquitin and ubiquitin mutants, in which surface residues that are known to interact with ubiquitin binding domains in interacting proteins are mutated (Phe-4, Leu-8, Ile-44, Asp-58, Val-70), we provide evidence that the ubiquitin-CXCR4 interaction follows a two-site binding mechanism in which the hydrophobic surfaces surrounding Phe-4 and Val-70 are important for receptor binding, whereas the flexible C terminus facilitates receptor activation. Based on these findings and the available crystal structures, we then modeled the ubiquitin-CXCR4 interface with the RosettaDock software followed by small manual adjustments, which were guided by charge complementarity and anticipation of a conformational switch of CXCR4 upon activation. This model suggests three residues of CXCR4 (Phe-29, Phe-189, Lys-271) as potential interaction sites. Binding studies with HEK293 cells overexpressing wild type and CXCR4 after site-directed mutagenesis confirm that these residues are important for ubiquitin binding but that they do not contribute to the binding of stromal cell-derived factor 1α. Our findings suggest that the structural determinants of the CXCR4 agonist activity of ubiquitin mimic the typical structure-function relationship of chemokines. Furthermore, we provide evidence for separate and specific ligand binding sites on CXCR4. As exogenous ubiquitin has been shown to possess therapeutic potential, our findings are expected to facilitate the structure-based design of new compounds with ubiquitin-mimetic actions on CXCR4.